Fenologi Pembungaan dan Pembuahan Berbagai Macam Berat Umbi Iles-Iles (Amorphophallus muelleri Blume) - Sumarwoto, Sumarwoto (Biota : Jurnal Ilmiah Ilmu-Ilmu Hayati, 2006)
The study about fruiting and flowering phenologies on various tuber weights of iles-iles has not been common yet. The fact was emphasized by Lingga et al. (1989) that most biologists and agronomists are not interested in doing research about the iles-iles, so the source is not easy to get. This research was aimed to studying the fruiting and flowering phenologies on various tuber weights of Iles-iles (Amorphophallus muelleri Blume). The experiment was done at Bogor Agricultural Institute experimental field, Darmaga at 250 m sea level height, from February 2000 to August 2002. The experimental design used was Completely Randomized Block Design with six replications. The treatment consist of four level of tuber weights, A = more than 1050 g; B = more than 700-1050 g; C = more than 350-700 g; D = less than or same as 350 g. The results showed that flowering of iles-iles occur on rainy season, after high rain intensity everydays. The higher tuber weights, compared with smaller tuber weights, produce bigger percentage of flower sprout, size of flower parts, flower size and fruit amount, and also total amount of embryo per stem. On the contrary, the percentage of vegetative sprout was produced more by lighter tuber. The flowering and fruiting on iles-iles, seem influenced by the interaction between tuber weight and the growth age of tuber.